A Single-Site Qualitative Study Exploring What Cancer Patients and Health Care Professionals Consider to be the Core Priorities in Relation to Psychosocial Cancer Care - Zoe Clothier MSc; Jenny Harris PhD; Agnieszka Kehinde MSc; Victoria Mumford MBA; Kate Upshon BSc; Clare Williamson MRes; Rachel MacArthur MSc; Rachel Stevenson DipHE; Sophie Otter MD(Res); May Teoh MD(Res); Jo Armes PhD (Cancer Control)
Introduction A cancer diagnosis often impacts emotional wellbeing, with patients frequently reporting unmet psychosocial needs throughout their care pathway. Needs-based support can help address these challenges, but barriers exist that limit its uptake by patients and its provision by health care professionals (HCPs). Identifying key aspects of psychosocial support and tailoring this to meet the preferences and priorities of the individual can enhance the patient-centredness of care, improving both patient outcomes and HCP job satisfaction. Aim This study aimed to explore what cancer patients and HCPs consider to be the core priorities in relation to psychosocial cancer care. Method Semi-structured interviews were conducted with cancer patients and HCPs at a single UK cancer centre to explore the research question. Interview transcripts were analysed using Framework Analysis to identify and interpret key themes. Results A total of 21 interviews (10 with patients, 11 with HCPs) were analysed. Six cross-cutting themes were generated from the data: personalised support, awareness and accessibility of support, patient-HCP communication, coordination of care, time and resource constraints, and ‘what matters most’ in psychosocial cancer care . HCP-specific themes were recognition of HCPs’ own psychosocial needs and the necessity for education and training in psychosocial care. Conclusion Psychosocial care is pivotal to cancer patients’ wellbeing and positively influences their perceptions of health, especially when this aligns with their individual needs and preferences. Cross-cutting themes highlighted the importance of holistic approaches addressing the multifaceted needs of patients and indicated alignment between patient and HCP care priorities. Supporting HCPs’ own wellbeing and providing appropriate training and skill development may further enhance the quality of psychosocial care delivery. Implementing a stepped-care approach may enable practitioners to better support their patients which in turn will improve their job satisfaction and patient outcomes.